INNOVATION FOR THE SUBJECT PRACTICAL ACTIVITIES OF THE PRIMARY SCHOOL OF WORKING TECHNOLOGIES WITH PLASTICS - TVARŮŽKA, Václav (Trends in education, 2018)
The paper deals with experience with extruded polystyrene as an alternative material suitable for practical activities of pupils at the primary school. Extruded polystyrene as a material is able to develop fine motor activities of pupils and their conceptual knowledge. Thanks to technological abilities, it is easy to work with it and its physical abilities enable its applications in a wide range of activities. The paper deals with technological possibilities of this material, its contribution for development of technical thinking and also risks that are possible to eliminate. In the paper are stated subjects and models for realizing the education of this topic. Integration of this material to education has a significant potential in recognizing of material characteristics and experiments.
Keywords: polystyrene; plastics; vocational education; practical activities; education; technologies